The Spectator, 2002-02-07 - Spectator, Valdosta State University (Valdosta State University, 2002)
Vol 70 Issue 4 - Born Digital Draft Copy. Budget Cuts Shared to Spare Academic Affairs -- Zaccari to Meet SAVE -- VSU Celebrates Black History -- Students Feel Free to Speak
The Spectator: The Unfiltered, Uncensored Voice of the Students
Born digital draft copy. Converted from QuarkXpress format to PDF. Some content may be incomplete from final print editions. Some fonts have been changed.
Keywords: Valdosta State University -- Periodicals